2020
DOI: 10.7150/ijms.48742
|View full text |Cite
|
Sign up to set email alerts
|

The Association Of Serum Cortisol Level With Microalbuminuria In Patients With Type 2 Diabetes And Prediabetes

Abstract: Whether cortisol secretion is linked with microalbuminuria remains undefined. We aimed to investigate the relationship between serum cortisol levels and the presence of microalbuminuria in patients with type 2 diabetes (T2DM) and prediabetes. A cross-sectional study was conducted with 211 patients with T2DM or prediabetes. Serum cortisol was measured at 8:00 h, 16:00 h, and 0:00 h. The level and circadian rhythm of ACTH were also evaluated. Urine excretion of albumin was measured. Patients were subdivided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
5
0
2
Order By: Relevance
“…Similar to our ndings, previous clinical studies con rmed cortisol and microalbuminuria in diabetic patients [7]. Koh et al found that urinary albumin excretion increased in more than 80% of patients with Cushing's syndrome and reversed after treatment [22].…”
Section: Cortisol and Albuminuriasupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our ndings, previous clinical studies con rmed cortisol and microalbuminuria in diabetic patients [7]. Koh et al found that urinary albumin excretion increased in more than 80% of patients with Cushing's syndrome and reversed after treatment [22].…”
Section: Cortisol and Albuminuriasupporting
confidence: 92%
“…The prevalence of hypercortisolism in diabetic patients was higher than that in the general population [5; 6]. Study indicated that cortisol was positively correlated with microalbuminuria in T2DM [7]. A small cross-sectional study suggested that cortisol might be a molecular marker for the severity of DR [8].…”
mentioning
confidence: 99%
“…In addition to the detrimental impact that concomitant hypertension exerts on the kidney, aldosterone may also impair glomerular filtration via other mechanisms. Zhang et al reported that even within the normal range, higher cortisol level was related to the development of microalbuminuria 34 . Therefore, further research should be conducted to explore the potential mechanism underlying adrenal hypertrophy on renal dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…По прогнозам, число людей с СД во всем мире увеличится с нынешних 463 миллионов до 700 миллионов к 2045 году, а вместе с ним и количество людей, у которых развиваются осложнения, связанные с СД [13]. Появляется все больше свидетельств того, что пол является важным фактором, определяющим эпидемиологию, патофизиологию, лечение и течение при многих заболеваниях, и, по-видимому, особенно актуален для неинфекционных заболеваний, в том числе, СД и рака.…”
Section: Discussionunclassified
“…Было обнаружено, что уровень кортизола положительно коррелировал с гликированным гемоглобулином (HbA1c), независимо от противодиабетических препаратов [21]. Однако результаты относительно взаимосвязи кортизола и кардиометаболических компонентов противоречивы [22].…”
Section: Discussionunclassified